1980
DOI: 10.1021/ed057p308.1
|View full text |Cite
|
Sign up to set email alerts
|

Purple benzene revisited

Abstract: A variant of the referenced demonstration using crown ethers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Moreover, since the early days of crown-ether chemistry, 18-crown-6 has been used to enhance the solubility of reactive potassium salts in organic media, e.g. KMnO 4 (Doheny & Ganem, 1980). [K(18c6)]OAc (OAc = acetate) has been shown to be useful as an acetylation agent for alkyl halides (Liotta et al, 1974), and over the past few years 'CECILs' (crown ether complex cation ionic liquids) such as [K(18c6)]OAc and [K(18c6)]OH gained in importance as basic catalysts for various organic transformations (e.g.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Moreover, since the early days of crown-ether chemistry, 18-crown-6 has been used to enhance the solubility of reactive potassium salts in organic media, e.g. KMnO 4 (Doheny & Ganem, 1980). [K(18c6)]OAc (OAc = acetate) has been shown to be useful as an acetylation agent for alkyl halides (Liotta et al, 1974), and over the past few years 'CECILs' (crown ether complex cation ionic liquids) such as [K(18c6)]OAc and [K(18c6)]OH gained in importance as basic catalysts for various organic transformations (e.g.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Because of the short preparation time and simple product workup, many students will have the opportunity to complete this experiment in less than one laboratory session. If so, this work can be used as a complement to experiments on crown ethers described in THIS JOURNAL (5,8) or elsewhere (9).…”
mentioning
confidence: 99%
“…• The oxidation of cyclohexene with KMnO 4 in benzene with either crown ether (18) or Aliquat 336 (19) as the LLPTcatalyst. It is found that the experimental procedure described in entry 5 can be used to oxidize cyclohexene.…”
Section: Resultsmentioning
confidence: 99%